ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR - Andini, Sophia (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to determine the factors that influence auditor switching in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2017 period. Design/methodology/approach- The population in this study were all companies listed on the Indonesia Stock Exchange in the period 2013 to 2017. The sample in this study was 188 companies, observations were obtained by purposive sampling method. The data analysis technique used is logistic regression analysis. Findings- The results showed that the variables of the audit opinion, public ownership, financial difficulties, and audit fees did not significantly influence the sample of companies to conduct auditor switching. Implications- The implication of the study results show that audit opinion, public ownership, financial distress, and audit fees are not determinants of audit switching so the explanation of the basis for audit dependency still needs to be reclassified through other factors. Subsequent research needs to expand the study area to other sectors and add periods of observation to obtain more comprehensive results. Keywords: Audit opinions, public ownership, financial distress, audit fees, and auditor switching.